Misconceptions about Women in Hemingway’s Novels - Kang, Chunxiao (INTI International University, 2020)
Ernest Hemingway depicted a lot of male characters who were always very strong either in body or in spirit, such as Santiago (in “THE OLD MAN AND THE SEA”) whereas the women in his novels are always neglected, but when going further with his works, many indispensable women in his novels were found, in contrast to men. This paper deals mainly with three different types of women in Hemingway’s works, his attitudes towards them and an analysis of why he had such attitudes towards them.